2016
DOI: 10.1159/000448335
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Outcomes of Patients with Concomitant Bladder and Urethral Carcinoma

Abstract: chronous BC was diagnosed in 13 (12%) patients, and the median follow-up was 21 months (interquartile range 4-48). Urethral cancers were of higher grade in patients with synchronous BC compared to patients with non-synchronous BC (p = 0.020). Patients with synchronous BC exhibited significantly inferior 3-year recurrence-free survival (RFS) compared to patients with non-synchronous BC (63.2 vs. 34.4%; p = 0.026). In multivariable analysis, inferior RFS was associated with clinically advanced nodal stage (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Recently published reports of cancer survival also confirmed the similar results. [ 20 , 21 ] In the present study, we found adjuvant chemotherapy was an important factor to improve OS in patients after RNU. Our oncological outcomes were in agreement with those of recent study series [ 22 ] but not in accordance with a cohort study in Korea.…”
Section: Discussionmentioning
confidence: 53%
“…Recently published reports of cancer survival also confirmed the similar results. [ 20 , 21 ] In the present study, we found adjuvant chemotherapy was an important factor to improve OS in patients after RNU. Our oncological outcomes were in agreement with those of recent study series [ 22 ] but not in accordance with a cohort study in Korea.…”
Section: Discussionmentioning
confidence: 53%
“…After reviewing the titles, abstracts and full texts, we selected 92 studies for qualitative synthesis (Fig. 1) [1,2,4–6,8–95].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, approximately 2-5% of patients with superficial and 40-60% with muscle-invasive bladder cancer develop urethral cancer later on [29]. In contrast, Gakis et al [30] reported one case (0.9%) of secondary bladder cancer 41 mo after initial therapy for PUC. Enlarged regional lymph nodes (LNs) are likely to represent metastatic disease (84%), making assessment of disease extent with pelvic magnetic resonance imaging for local staging obligatory [13,31,32].…”
Section: Diagnostic Evaluation and Stagingmentioning
confidence: 99%